2009
DOI: 10.1093/schbul/sbp011
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Soft Signs in Schizophrenia: A Meta-analysis

Abstract: NSS occur in a majority of the schizophrenia patient population and are largely distinct from symptomatic and cognitive features of the illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
130
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(148 citation statements)
references
References 106 publications
11
130
0
4
Order By: Relevance
“…Evidence for schizophrenia as a neurodevelopmental disorder is consistent with a number of findings in patients with schizophrenia such as minor physical anomalies (Weinberg, et al 2007), neurological soft signs (Chan, et al 2009), reduced brain asymmetry (Sommer, et al 2001) and an increased rates of obstetric complications (Geddes, et al 1999). Static volumetric deficits in brain structure have been cited as supporting the neurodevelopmental hypothesis of schizophrenia so progressive changes are problematic to an exclusively neurodevelopmental theory.…”
Section: Sensitivity Analysissupporting
confidence: 62%
“…Evidence for schizophrenia as a neurodevelopmental disorder is consistent with a number of findings in patients with schizophrenia such as minor physical anomalies (Weinberg, et al 2007), neurological soft signs (Chan, et al 2009), reduced brain asymmetry (Sommer, et al 2001) and an increased rates of obstetric complications (Geddes, et al 1999). Static volumetric deficits in brain structure have been cited as supporting the neurodevelopmental hypothesis of schizophrenia so progressive changes are problematic to an exclusively neurodevelopmental theory.…”
Section: Sensitivity Analysissupporting
confidence: 62%
“…Findings concerning cerebellar aberration have been controversial in schizophrenia, unlike ASD (Bottmer et al, 2005). In schizophrenia, cerebellar disturbances contribute to neurological soft signs, such as observable defects in sensory integration, motor coordination, and behavioral inhibition, which are largely distinct from the core symptoms (Bottmer et al, 2005;Chan et al, 2010;Shinn, et al, 2015). Accordingly, it is unlikely that cerebellar aberration is associated with cognitive deficits in schizophrenia.…”
Section: Social Cognitive Deficits In Schizophreniamentioning
confidence: 99%
“…Previous clinical and neuroimaging studies identified a higher prevalence of NSS in individuals with schizophrenia at any stage of their illness and in their first-degree relatives [2,3,4,5]. Moreover, increased NSS scores have been shown to correlate with the clinical course of the disease in general and psychopathological symptoms in particular [6].…”
Section: Introductionmentioning
confidence: 99%